Expression of localization in the translations of Georg Wenker’s fourth sentence - Kardelytė-Grinevičienė, Daiva (Lietuvių kalba, 2019)
This study examines the variation of the means of expressing localisation in different translations of one German sentence into Lithuanian. The main instrument of the analysis is one of the forty German sentences created in the 19th century by Georg Wenker, the pioneer of linguistic geography. The choice of this sentence was determined by its distinctiveness as it features specific characteristics of the Landmark and the interrelations between complex spatial scenes realised in it. The Lithuanian translations of the original German sentence were obtained by means of an electronic questionnaire. The goals of the study are to examine the inventory of the means of expressing localisation with respect to the parameter of the translator’s dialect and to verify the proposition made in prior studies of the Lithuanian translations of Wenker’s data that the variation of the means of expressing localisation is determined by the complex spatial scenes realised in the original sentence. A general evaluation of the newly acquired data and its analysis seems to confirm the proposition that the complex spatial scenes realised in the original sentence play a key role in determining the variation of the means of expressing localisation in the Lithuanian translations of Wenker’s fourth sentence. A comparison of the data acquired for the present study with the material obtained by Wenker in the 19th century leads to a conclusion that the linguistic inventory utilised to express spatial relations in the Lithuanian translations is essentially the same, i.e. Lithuanian prefers prepositional constructions as the prototypical means of rendering spatial relations. However, the newly obtained material contains more cases which indicate the possible influence of the translator’s dialect in the choice of the means of expressing localisation (cf. the use of the illative case, specific lexemes, etc.). In addition, the data collected for the present study also exhibits a greater variability of the means of expressing localisation used to refer specific spatial scenes. This could have been determined by the factor of subjectivity, namely, by the tendency of the respondents of this study to interpret the original sentence with greater freedom in comparison to its interpretation by the participants of Wenker’s study.